Enkele metodologiese implikasies van hedendaagse vakfilosofiese kwessies rondom die Historiese Opvoedkunde - Postma, Willem (Koers, 1992)
Contemporary topical historico-educational issues force the educational historian to reflect repeatedly on both the study method and the subject philosophy underlying the choice and application of the latter method. It is argued that a thorough knowledge of and insight into certain historico-educational subject philosophical bases which determine the choice and application of the method of history of education can lead to more valid and reliable conclusions and findings in the field of the history of education.